Clinical manifestations of COVID‐19 differ by age and obesity status. Issue 2 (19th October 2021) - Cheng, Wesley A.; Turner, Lauren; Marentes Ruiz, Carolyn J.; Tanaka, Melissa L.; Congrave‐Wilson, Zion; Lee, Yesun; Jumarang, Jaycee; Perez, Stephanie; Peralta, Ariana; Pannaraj, Pia S.
Abstract: Background: Age and obesity status are associated with severe outcomes among hospitalized individuals with COVID‐19. It remains unclear whether age and obesity are risk factors for milder COVID‐19 illness. Methods: We prospectively enrolled SARS‐CoV‐2‐exposed individuals. Participants recorded symptoms for 28 days and were tested for SARS‐CoV‐2 by reverse transcription polymerase chain reaction (RT‐PCR) and serology. Type, number, and duration of symptoms and SARS‐CoV‐2 laboratory parameters were compared by age and obesity status. Results: Of 552 individuals enrolled from June 2020 to January 2021, 470 (85.1%) tested positive for SARS‐CoV‐2 including 261 (55.5%) adults ≥18 years, 61 (13.0%) adolescents 12–17 years, and 148 (31.5%) children <12 years. Children had fewer symptoms (median 2 vs. 3, p < 0.001) lasting fewer days (median 5 vs. 7, p < 0.001) compared with adolescents/adults. Body mass index of 300 (63.8%) individuals classified with overweight or obesity (OWOB). Individuals with OWOB suffered more symptoms compared with individuals without OWOB (median 3 vs. 2, p = 0.037), including more cough and shortness of breath ( p = 0.023 and 0.026, respectively). Adolescents with OWOB were more likely to be symptomatic (66.7% vs. 34.2%, p = 0.008) and have longer respiratory symptoms (median 7 vs. 4 days, p = 0.049) compared with adolescents without OWOB. Lower RT‐PCR Ct values were found in children and symptomatic individuals compared with adolescent and adults and asymptomatic individuals, respectively ( p = 0.001 and 0.022). Conclusions: Adolescents and adults with OWOB experience more respiratory symptoms from COVID‐19 despite similar viral loads. These findings underscore the importance of vaccinating individuals with OWOB.